Financing lifelong learning - Oosterbeek, Hessel [Verfasser]; Patrinos, Harry Anthony [Verfasser] (My University, 2009)
"This paper describes and analyzes different financial schemes to promote lifelong learning. Positive effects of financial incentives to pupils are not restricted to high ability pupils, as low ability students also seem to benefit. The evidence regarding the effects of subsidy forms is limited. The most prominent knowledge gaps regarding the effects of various financing schemes related to lifelong learning are the effects of vouchers; financial aid schemes for students; and entitlements and individual learning accounts." (Autorenreferat, BIBB-Doku)
Keywords: S 4.1 Finanzierungsquellen; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; Bildungsinvestition; Lebenslanges Lernen; Weiterbildungsfinanzierung; Bildungsgutschein; Lernzeitkonto